2018
DOI: 10.7567/jjap.57.08ra01
|View full text |Cite
|
Sign up to set email alerts
|

Present status and future perspectives of bifacial PERC+ solar cells and modules

Abstract: This paper reviews the main research results related to PERC+ silicon solar cells. Compared to today's industry typical passivated emitter and rear cell (PERC) silicon solar cells with full-area rear aluminum layer, PERC+ solar cells apply an aluminum finger grid on the rear side and hence are able to absorb diffuse light from the rear side in addition to the direct sunlight which is absorbed from the front side. This bifaciality increases the energy yield of silicon solar modules by up to 25%. Since its first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…2 . One should note that the bifaciality of PERC+ in the range of 80% 54 allows for a significantly increased energy yield (10–20% 55 ) for utility applications. This has to be taken into account when comparing the performance with other cell structures with higher or lower bifaciality.…”
Section: Resultsmentioning
confidence: 99%
“…2 . One should note that the bifaciality of PERC+ in the range of 80% 54 allows for a significantly increased energy yield (10–20% 55 ) for utility applications. This has to be taken into account when comparing the performance with other cell structures with higher or lower bifaciality.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, n-type silicon cells exhibit low recombination losses compared to p-type silicon cells, such that the former is more suitable for use in a bifacial cell configuration than the latter. Multi-wire busbar technology is attracting more attention due to the reduced resistance and enhanced light absorption associated with this approach due to increased light scattering [10]. Recently, our research group reported outdoor field test results indicating a bifacial gain in excess of 30% from a 60-cell n-type silicon bifacial module oriented to the south at an installation angle of 30 • [11], and a bifacial gain of 14.5% from a 1.8 kW bifacial PV system [12].…”
Section: Introductionmentioning
confidence: 99%
“…When paired with the development of transparent back contacts, bifacial Si devices efficiencies of 19.5−22% and 17−19% have been achieved when illuminated through the front and rear of the device, respectively. 13 These values result in a bifaciality, defined as the ratio of efficiency illuminated through the back to efficiency illuminated through the front, of 85%.…”
mentioning
confidence: 99%